Relationship between lightning flash rates and radar observations from Colorado and Australia - Ryan, Jesse James, author; Rutledge, Steve A., author (Colorado State University. Libraries, 1999)
Relationships between lightning flash rates and radar observations were examined for two regions; northeastern Colorado and Darwin, Australia. Five case studies from Colorado were analyzed using observational data from: the CSU-CHILL multiparameter radar, the ONERA VHF lightning interferometer, a field change meter and the National Lightning Detection Network. Three case studies from tropical Australia were analyzed using data from: the C-POL BMRC/NCAR multiparameter radar, a field change meter and an Advanced Lightning Detection Finder network. For each case, parameters such as peak echo height (H), storm area (A), and storm volume (V) were computed using different radar reflectivity and temperature thresholds. Storm areas and volumes were computed above the altitude of various temperature thresholds. Cloud echo-top height (Ho) was defined as the peak height using the O dBZ reflectivity threshold. Correlations existed between H, A, and V, and the total lightning flash rate on a majority of the cases and were strongest when higher reflectivity and colder temperature thresholds were used. An increased correlation between H, A, and V, and total flash rate for high reflectivity (> 20 dBZ) thresholds was noted for storms which contained broad areas of stratiform precipitation. Since stronger correlations were found between total flash rate and the product of A and V (AV) than between the total flash rate and H5, this study suggests that significant error can be introduced by assuming that the horizontal scale of a thunderstorm charge generation is comparable to the vertical scale. In addition, we show that AV and H5 at high reflectivities (> 20 dBZ) are both better correlated to total flash rate than H/, a parameter commonly used as a predictor for lightning flash rates in modeling studies. The ratio of intracloud (IC) to cloud-to-ground (CG) lightning was also analyzed for each case. This ratio was subsequently compared to cold cloud thickness (CCTh), defined as the distance between cloud top and the environmental freezing level. The relationships between IC/CG ratio and CCTh were similar to prior research, except for storms with high (> 40) IC/CG ratios.
Summer 1999.
Also issued as Jesse James Ryan's thesis (M.S.) -- Colorado State University, 1999.
Keywords: Lightning -- Colorado; Lightning -- Australia; Radar meteorology